2011
DOI: 10.1002/ddrr.1104
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Infant Spontaneous General Movements as Predictors of Developmental Disabilities

Abstract: The challenge of identifying infants who are at risk for developmental delay and possible adverse neurodevelopmental outcome demands methods of evaluation that will lead to early intervention to minimize developmental disability and to maximize the infant's potential. A qualitative assessment of spontaneous general movements (GMs) in the preterm, term, and young infant at risk is a valid and reliable tool for evaluation (Prechtl [1990] Early Hum. Dev. 23:151-158). The aim of this review is to describe the theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 77 publications
(147 reference statements)
0
30
0
7
Order By: Relevance
“…Perinatal assessment of GMs is a reflection of the integrity of nervous system (37). Fetal and infant GMs might provide useful information for predicting neurodevelopmental disabilities (38). This study found that of the 10 fetal movement patterns, GM was the only one movement pattern whose frequency was positively related to gestational age (11-14 week).…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal assessment of GMs is a reflection of the integrity of nervous system (37). Fetal and infant GMs might provide useful information for predicting neurodevelopmental disabilities (38). This study found that of the 10 fetal movement patterns, GM was the only one movement pattern whose frequency was positively related to gestational age (11-14 week).…”
Section: Discussionmentioning
confidence: 99%
“…The voluntary movement gradually supersedes general movement after 3 months of age, which corresponds with the decrease of the SP layer, suggesting that general movement is a reflection of spontaneous activity in early-born neurons including SpNs (Bayatti et al, 2008;Hadders-Algra, 2018). Many studies have reported that observation of general movement could be useful to predict developmental delay or autism that may occur at later ages (Zuk, 2011;Kanemaru et al, 2013;So et al, 2016;Gima et al, 2018). Moreover, the finding that genes expressed in a subplate-specific manner in mice are significantly associated with autism spectrum disorders and schizophrenia supports the notion that general movement in fetuses and neonatal human babies is a reflection of the spontaneous activity of SpNs.…”
Section: Subplate Function and Brain Developmental Disordersmentioning
confidence: 99%
“…These behaviors individually have been shown to be important for early learning and development and to relate to future neuromotor and cognitive outcome. 22,29,31 However, what is even more interesting and important for clinicians is to recognize that these behaviors are highly interrelated and impact one another dynamically in early development. 16,80 Thus intervention to address future developing skills such as object manipulation skills should not wait until infants are older or have begun to show delayed performance of these skills.…”
Section: 0 Conclusionmentioning
confidence: 99%